2001
DOI: 10.1039/b106881b
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroaryl boryl complexes: synthesis, spectroscopic and structural characterisation of a complex containing the bis(pentafluorophenyl)boryl ligand

Abstract: The synthesis, spectroscopic and structural characterisation of the bis(pentafluorophenyl)boryl derivative CpFe-(CO)2B(C6F5)2 are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The multinuclear NMR data of 5-8 in solution meet the expectations, showing for example considerably deshielded 11 B NMR resonances with respect to those of the aminoborane precursors at δ = 79.2 (5), 80.0 (6), 79.7 (7) and at δ = 55.5 (8). The smaller boranes 5, 6, and 8 display single sets of signals for the ER 3 -ligand in the 1 H and 13 C NMR spectra, thus proving free rotation with respect to the B-E bond in solution.…”
Section: Results and Discussion (Dichloro)silyl-and -Germylboranessupporting
confidence: 74%
See 1 more Smart Citation
“…The multinuclear NMR data of 5-8 in solution meet the expectations, showing for example considerably deshielded 11 B NMR resonances with respect to those of the aminoborane precursors at δ = 79.2 (5), 80.0 (6), 79.7 (7) and at δ = 55.5 (8). The smaller boranes 5, 6, and 8 display single sets of signals for the ER 3 -ligand in the 1 H and 13 C NMR spectra, thus proving free rotation with respect to the B-E bond in solution.…”
Section: Results and Discussion (Dichloro)silyl-and -Germylboranessupporting
confidence: 74%
“…Boryl complexes L x M-BR 2 (R = alkyl, aryl) without ligand-to-boron πinteraction are very rare, but have received significant interest in studies, which addressed the nature of the metal-boron linkage and the role of metal-boron π-interaction in particular. 1,7 Due to the obvious difficulties accompanying the synthesis of alkyl-and arylboryl complexes, corresponding silyl-or germylboranes could provide a useful alternative.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to develop synthetic routes to metal complexes containing the B(C 6 F 5 ) 2 ligand, Aldridge and coworkers synthesized [207] FpB(C 6 F 5 ) 2 (Scheme 143). Complexes containing C 6 H 5 -like moieties show potential as highly acidic Lewis acids at the boron centers and thus may serve as useful probes for possible boryl ligands to act as -acids.…”
Section: Fe-hg Bond Formationmentioning
confidence: 99%
“…In 1990, an early beautiful example of type D LA-TM complex was reported by Baker et al [43] (46 in Figure 23), in which a typical TM=B double bond was formed by donating the electron pair of iridium to boron's empty p z orbital. Later, Hartwig [44] and Aldridge et al [45] reported the synthesis and structure of type D biarylboryl complexes CpFe(CO) 2 B(Ar) 2 (47) (Figure 23). A rare example of type D dialkylboryl tungsten complex 48 with -H agostic interaction was reported by Pritzkow et al [46] As for type E sp 2 boron-based LA-TM complexes, only very few examples have been found until now.…”
Section: Sp 2 Boron-based La-tm Complexesmentioning
confidence: 99%